LINGUISTIC ANALYSIS OF PROVERBS AS A PHENOMENON OF FOLKLORE - Mukhtarova, Rezeda; Tsyganova, Evgenia; Radionova, Svetlana (Revista Inclusiones, 2020)
Folklore in linguistic cultures is represented in different spectra of the language, but the most vivid is the level of proverbs, sayings and aphorisms. For this reason proverbs and sayings have always attracted attention of scholars in our country and abroad. A lot of linguistic research is dedicated to this reach level of language. However the gender approach to analyzing folklore in different linguistic cultures has not been applied before. In this paper we make an attempt to analyze the proverbs with gender component in English and Tatar linguistic cultures languages from the point of view of their proverbial markers, particularly their outer form, semantic mechanisms of their formation, syntactic structure and consequently the national peculiarities of proverbs in the English and Tatar languages. In this work we use comparative method to provide the linguistic description of the proverbs with gender component so that to identify such markers as their phonic means, syntactic structure and semantic mechanisms of formation.